Business and policy models to incentivise utilities to engage with demand-side management - Peter Warren (Green Finance, 2019)
Business and policy models to incentivise utilities to engage with demand-side management (DSM) have received more attention in the grey literature than the academic literature. This review paper contributes to filling this gap by reviewing theoretical frameworks for four key categories of business models and how they relate to policy models that enable their implementation. The paper proposes a theoretical lens through which to visualise the different frameworks. The review discusses the key benefits and challenges for utilities to engage with DSM, and finds that deferred investment in new generation capacity, new business opportunities and services, and dealing with variable power production are the primary benefits, and limited incentives to invest in markets based on the quantity of energy sold and cost recovery issues (such as DSM programme costs) are the main challenges. The paper reviews four primary business and policy models: decoupling, demand-side participation in capacity markets, utility obligations and Energy Service Companies (ESCOs), and finds that despite the limitations of the evidence base on the applicability of decoupling in fully liberalised markets, demand-side participation in capacity markets, utility obligations and ESCOs appear to be applicable across contexts.